User Centred Design model (G2C2G) for rural e-governance projects. (21st December 2009) - Malhotra, Charru; Chariar, Vijayaraghavan M.; Das, Lalit K.
ICT has the potential to spawn innovative means of wealth generation in rural areas by providing timely information and public services. However an in-depth analysis of RASI in Tamil Nadu State of India, indicates that such e-government projects are usually designed from the perspective of bureaucrats, technocrats or donor bodies rather than from the perspective of the villagers. Based on a User Centred Design (UCD) approach, this paper proposes an inclusive strategy, titled Government to Citizen to Government (G2C2G), for designing rural e-governance projects that could address the needs of both the government and the governed.